The effect of side chain engineering on conjugated polymers in organic electrochemical transistors for bioelectronic applications. Issue 7 (7th January 2022) - He, Yifei; Kukhta, Nadzeya A.; Marks, Adam; Luscombe, Christine K.
Abstract : The versatile synthetic side chain toolbox assists in tuning the OECT parameters by controlling material properties of organic mixed conductors. In this review we critically summarise and evaluate various side chains used throughout OECT materials. Abstract : Bioelectronics focuses on the establishment of the connection between the ion-driven biosystems and readable electronic signals. Organic electrochemical transistors (OECTs) offer a viable solution for this task. Organic mixed ionic/electronic conductors (OMIECs) rest at the heart of OECTs. The balance between the ionic and electronic conductivities of OMIECs is closely connected to the OECT device performance. While modification of the OMIECs' electronic properties is largely related to the development of conjugated scaffolds, properties such as ion permeability, solubility, flexibility, morphology, and sensitivity can be altered by side chain moieties. In this review, we uncover the influence of side chain molecular design on the properties and performance of OECTs. We summarise current understanding of OECT performance and focus specifically on the knowledge of ionic–electronic coupling, shedding light on the significance of side chain development of OMIECs. We show how the versatile synthetic toolbox of side chains can be successfully employed to tune OECT parameters via controlling the material properties. As the field continues to mature, more detailed investigations into the crucial role side chain engineering plays on the resultant OMIEC properties will allow for side chain alternatives to be developed and will ultimately lead to further enhancements within the field of OECT channel materials.